Forest regeneration in abandoned logging roads in lowland Costa Rica - Guariguata, Manuel R.; Manuel, R.; Dupuy, J.M. (1997)
This study characterised plant regeneration in four old logging roads (700-1 000 m long) in selectively logged forests in lowland Costa Rica, 12-17 years after abandonment. Sets of 4 m2 plots were laid out at 20 m intervals in three distinct microhabitats: road track (topsoil eliminated), road edge (where removed topsoil accumulates on the sides after road construction), and adjacent logged forest. Density of stems taller than 1 m and at least 5 cm dbh (included canopy trees, midstorey trees, lianas, palms, shrubs and tree fern species) was highest in the road edge plots than either the track or logged forest plots. This ‘edge effect’ is presumably due to buried seed germination of light-demanding trees and shrubs after moderate soil disturbance, less compaction and higher substrate fertility than in road tracks. Species richness was the lowest, but relative dominance the highest, in the track plots of all roads: 6-9 species comprised alone 50% of the Importance Value Index (IVI), in contrast to 11-15 and 16-22 species required to reach 50% IVI in edge and forest plots, respectively. There was evidence of soil compaction in tracks in three out of four roads which, in addition to low substrate fertility and initial lack of on-site plant propagules, could explain slower recovery of stem density and species richness compared to edge and logged forest plots. For stems between 5 20 cm dbh, density and basal area in the track plots averaged about one-fourth of edge and logged forest plot values. We estimated recovery of basal area in road tracks to take at least 80 years to reach the status found in logged forest, and species richness over an even longer period. We suggest that abandoned logging roads serve as long corridors of relatively uniform and long-la sting floristic and structural characteristics that may confer particular ecological roles in selectively logged forests.